After All These Years - Isaacs, Susan (New York Harpper Collins Publishers, 1993)
Rosie Meyers does not give up hope that her estranged husband Richie will reconsider divorcing her until she trips over his corpse in the kitchen. The fact that she tries to yank the knife from his body seals her fate as the prime suspect. Realizing that the real killer's trail is growing cold, Rosie dodges the cops while trying to wrest the truth out of Richie's friends and associates. Strong language and some explicit descriptions of sex. 1993
Keywords: Executives' spouses -- Women